BEBERAPA ASPEK BIOLOGI IKAN SIDAT (Anguilla spp.) DI SUNGAI KETAHUN, PROVINSI BENGKULU - Samuel, Samuel; Adjie, Susilo (Faculty Fisheries Departement Fisheries, 2004)
Study on some biological aspect of freshwater eel in the Ketahun river, Bengkulu Province was conducted in 1997. Four stations were set up by using purposive sampling method. The objective of this study was to obtain some information on biological aspect of freshwater eel such as length-weight relationships, characteristic of natural growth, condition factor, food habit and water quality. Results showed that there was definitely one species of sidat encounted in the Ketahun river i.e : Anguilla marmorata called âpelus kembangâ. The characteristic of natural growth was isometric with b value of 2,32-3,43, and condition factor of 1,065-1,200. Based on their feeding habit, this freshwater eel (Anguilla marmorata) can be grouped in carnivorous fish. Water quality condition of the Ketahun river can still support freshwater ellâs life.Keywords: biological aspects, freshwater ell (Anguilla spp.), Ketahun river Bengkulu